Cassava (Manihot esculenta Crantz): A Systematic Review for the Pharmacological Activities, Traditional Uses, Nutritional Values, and Phytochemistry - Mohidin, Siti Raudhah Noor Shifa Putri; Moshawih, Said; Hermansyah, Andi; Mohd Ikmal, Asmuni; Shafqat, Naeem; Long, Chiau Ming * (SAGE Publications, 2023)
Cassava (Manihot esculenta Crantz) is considered one of the essential tuber crops, serving as a dietary staple food for various populations. This systematic review provides a comprehensive summary of the nutritional and therapeutic properties of cassava, which is an important dietary staple and traditional medicine. The review aims to evaluate and summarize the phytochemical components of cassava and their association with pharmacological activities, traditional uses, and nutritional importance in global food crises. To collect all relevant information, electronic databases; Cochrane Library, PubMed, Scopus, Web of Science, Google Scholar, and Preprint Platforms were searched for studies on cassava from inception until October 2022. A total of 1582 studies were screened, while only 34 were included in this review. The results of the review indicate that cassava has diverse pharmacological activities, including anti-bacterial, anti-cancer, anti-diabetic, anti-diarrheal, anti-inflammatory, hypocholesterolemic effects, and wound healing properties. However, more studies that aim to isolate the phytochemicals in cassava extracts and evaluate their pharmacological property are necessary to further validate their medical and nutritional values.